2016
DOI: 10.1007/s13538-016-0420-9
|View full text |Cite
|
Sign up to set email alerts
|

Exact Solutions of the Gardner Equation and their Applications to the Different Physical Plasmas

Abstract: How to citeComplete issue More information about this article Journal's homepage in redalyc.org Scientific Information System Network of Scientific Journals from Latin America, the Caribbean, Spain and Portugal Non-profit academic project, developed under the open access initiative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The general form of NLPDEs that contain two or more independent variables which we consider to explore the solutions by using (G ′ /G, 1/G)-expansion method [52,53] can be written as follows:…”
Section: (G ′ /G 1/g)-expansion Methodsmentioning
confidence: 99%
“…The general form of NLPDEs that contain two or more independent variables which we consider to explore the solutions by using (G ′ /G, 1/G)-expansion method [52,53] can be written as follows:…”
Section: (G ′ /G 1/g)-expansion Methodsmentioning
confidence: 99%
“…Here we have used the (1⁄G' )-expansion method [12] for calculating the exact solutions. Balancing the terms U' and U 2 in Eq.…”
Section: Exact Solution With (1⁄g' )-Expansion Methodsmentioning
confidence: 99%
“…As a pioneer work Li et al [15] has applied the two-variable (G ′ /G, 1/G)-expansion method and found the exact solutions of Zakharov equations. Some applications of the (G ′ /G, 1/G)-expansion method can be seen in [16,17,18,19,20]. (1/G ′ )-expansion method introduced by Yokus [21] firstly.…”
Section: Introductionmentioning
confidence: 99%
“…(1/G ′ )-expansion method introduced by Yokus [21] firstly. Some applications of the (1/G ′ )-expansion method can be seen in [20,22].…”
Section: Introductionmentioning
confidence: 99%